Conservative Treatment Alone and with Diclofenac Sodium Phonophoresis on The Patients With Low Back Pain Due to Prolapsed Lumbar Intervertebral Disc - Rahman, H N Masuk; Haque, Asiful; Emran, Mohammed; Zaman, A K Ahmad (KYAMC Journal, 2022)
Background: Prolapsed lumbar intervertebral disc (PLID) one of the major causes of low back pain. The PLID has become an important and increasingly general health problem, both in Bangladesh and across the world. Phonophoresis has been used clinically since the early 1960s in attempts to drive these drugs transdermally into subcutaneous tissues. The efficacy of Phonophoresis has not been conclusively established in PLID linked low back pain. Objective: To evaluate the effects of Diclofenac Sodium Phonophoresis on patients with low back pain due to PLID. Materials and Methods: The comparative study was conducted on the 72 patients diagnosed as PLID after being confirmed by Magnetic Resonance Imaging (MRI) and, were randomly assigned to Group A(Control group) and Group B (Case group), 36 patients in each group. Visual analog scale (VAS), Straight leg raising (SLR) test used to assess the effects on the last 3rd day of the consecutive week. Results: There were significant differences of improvement in outcome measure between the two groups from pretreatment to week 4. After 4 weeks of treatment VAS score in Group A was 2.10±0.5 and in Group B was 1.7 ± 0.5,P-Valuewas0.026.The significant improvement was observed in Group B patients, and according to Straight leg raising test of patients in Group A was 65.27± 7.36 and for group B it was 75.1 ±6.9. P-Value of 0.069 implies that it was not significant. Conclusion: Effectively managed Diclofenac sodium Phonophoresis can reduce the pain consistency of PLID to a major extent. KYAMC Journal Vol. 13, No. 03, October 2022: 158-164